Development of Modern Marathons and Distance Running - Sasho Belovski (Karolinum Press, 2014)
This work attempts to present the birth, development, and diffusion of modern marathon and distance running. Ancient stories and initial beginnings are fairly mentioned, but without any attempt to analyze in details the early forms of running. Instead, a more accurate study starts with the last decades of the 19th century which are being considered as crucial period for what will later become a new phenomenon of today's modern society. The research approach relies on qualitative analysis and it's characterized, besides existing literature, with personal interviews with key figures from the area of interest. It further contains short case studies that help to understand different aspects that contributed to the expansion and improvement of the industry of marathon and running in general. Part of the analysis will be also focused on the Czech Republic, so that this work gains larger local relevance and applications. Modern marathon and distance running is experiencing rapid growth and gains larger importance among various stakeholders. It can be said that the knowledge about its recent development is not very extensive, even among people that practice it or are directly and indirectly involved. The aim of this work, thus, is to offer selected highlights of its modern beginnings which should serve not just enthusiastic runners and organizers of marathon and long distance running events, but also historians, students, and academics as source of useful information and base for further academic works. Vývoj moderních maratonů a distančního běhu Tato práce si dává za cíl prezentovat vznik, vývoj a šíření moderního maratonu a distančního běhu. Práce se rovněž okrajově dotýká prvních historických pramenů v oblasti běhu, avšak podrobná analýza jeho raných forem není jejím účelem. Detailnější studie je naopak věnována období počínajícímu posledními dekádami 19. století, které zásadním způsobem předznamenaly vývoj směřující ke vzniku nového fenoménu dnešní moderní společnosti. Způsob výzkumu je založen na kvalitativní analýze a kromě využití existující odborné literatury je charakteristický především osobními rozhovory s klíčovými osobnostmi z oblasti distančního běhu. Práce dále obsahuje krátké případové studie umožňující lepší pochopení jednotlivých aspektů, které přispěly k expanzi a pokroku v oblasti maratonu a běhu obecně. Část analýzy se zaměřuje konkrétně na Českou republiku, aby tak mohla mít co nejširší lokální význam a využitelnost. Moderní marathon a distanční běh zažívají výrazný rozmach a přitahují stále větší zájem všech zainteresovaných osob - stakeholderů běžeckého sportu. Můžeme však konstatovat, že mezi aktivními běžci jakož i mezi dalšími lidmi, kteří jsou přímo či nepřímo s distančním během spojeni, nejsou vědomosti o jeho současném rozvoji příliš hluboké. Tato práce chce nabídnout vybrané, zásadní události moderní historie distančního běhu, a sloužit tak nejen zaníceným aktivním běžcům a organizátorům běžeckých závodů, ale též historikům, studentům a akademikům jako zdroj užitečných informací a základ pro budoucí vědeckou činnost.